Characterization of the animal by-product meal industry in Costa Rica: Manufacturing practices through the production chain and food safety. (19th March 2018) - Leiva, A; Granados-Chinchilla, F; Redondo-Solano, M; Arrieta-González, M; Pineda-Salazar, E; Molina, A
ABSTRACT: Animal by-product rendering establishments are still relevant industries worldwide. Animal by-product meal safety is paramount to protect feed, animals, and the rest of the food chain from unwanted contamination. As microbiological contamination may arise from inadequate processing of slaughterhouse waste and deficiencies in good manufacturing practices within the rendering facilities, we conducted an overall establishment's inspection, including the product in several parts of the process. An evaluation of the Good Manufacturing Practices (GMP) was carried out, which included the location and access (i.e., admission) to the facilities, integrated pest management programs, physical condition of the facilities (e.g., infrastructure), equipments, vehicles and transportation, as well as critical control points (i.e., particle size and temperature set at 50 mm, 133°C at atmospheric pressure for 20 min, respectively) recommended by the OIE and the European Commission. The most sensitive points according to the evaluation are physical structure of the facilities (avg 42.2%), access to the facilities (avg 48.6%), and cleaning procedures (avg 51.4%). Also, indicator microorganisms ( Salmonella spp., Clostridium spp., total coliforms, E. coli, E. coli O157:H7) were used to evaluate the safety in different parts of the animal meal production process. There was a prevalence of Salmonella spp. of 12.9, 14.3, and 33.3% in Meat and Bone Meal (MBM), poultry by-products, and fish meal, respectively. However, there were no significant differences ( P = 0.73) in the prevalence between the different animal meals, according to the data collected. It was also observed that renderings associated with the poultry industry (i.e., 92.0%) obtained the best ratings overall, which reflects a satisfactory development of this sector and the integration of its production system as a whole.